Characterization of hopanes in surface sediments from Southwest corner of South China Sea: application of PCA utilizing of individual hopanes - Ismail, N.; Zakaria, M.P.; Abdullah, A.H.; Mohamed, C.A.R.; Sukri, N.S.; Manan, N.; Masood, N.A.; Juahir, H. (University Kebangsaan Malaysia, 2013)
Oil pollution has been introduced into the aquatic environment of the South China Sea through anthropogenic activities such as discharging of oil during extraction, transportation and consumption. In order to determine the source of oil pollution in South China Sea, 30 surface sediment samples were collected in 2008 and were analyzed for pentacyclic triterpanes (hopane) by gas chromatography mass spectrometer (GCMS) with m/z 191. This study investigates the utility and limitation of individual hopane in tracing the sources of oil pollution by using Principle Component Analysis (PCA). Characterization the utility of hopane in determining the source of oil pollution has been done by integrating diagnostic ratios of C29/C30 and ΣC31-C35/C30 with PCA. PCA has classified all target components into 3 major principle components prior to determine their importance in identifying the source of oil pollution. From the rotated component pattern, first principle component (63.24% of variability) loaded by 9 target compounds which namely Ts, Tm, 17α(H), 21β(H)- norhopane, 17α(H), 21β(H)- hopane, 22S, 17α(H), 21β(H)- homohopane, 22S, 17α(H), 21β(H)- bishomohopane, 22S, 17α(H), 21β(H)- trishomohopane, 22S, 17α(H), 21β(H)- tetrakishomohopane and 22S, 17α(H) and 21β(H)- pentakishopane. Those individual hopanes listed in PC1 were excellent in tracing both oil pollution as all of them degrade less and generally unaffected by even severe biodegradation. This findings give better understanding for non consideration of both 17β(H), 21α(H)- norhopane, 17β(H), 21α(H)- hopane in determining the origin of oil spill.